Comparison of two different electrodialytic cells for separation of phosphorus and heavy metals from sewage sludge ash. (April 2015) - Ebbers, Benjamin; Ottosen, Lisbeth M.; Jensen, Pernille E.
Highlights: A new electrodialytic remediation method for a nutrient rich waste stream is investigated. Reduction of compartments in experimental setup increases overall efficiency. Removal of heavy metals was faster and increased significantly in the new setup. Mobilization of phosphorus was faster and increased significantly in new setup. Abstract: With decreasing availability of phosphorus from primary resources its recovery from waste streams becomes increasingly more important. Sewage sludge ash is rich in phosphorus, but the direct use as fertilizer is limited because of inorganic contaminants such as heavy metals and strong bonding of phosphorous in the ash. Electrodialysis (ED) can be used to recover phosphorus and simultaneously remove heavy metals. The present work is an experimental screening of different options for ED in relation to experimental setup and combination with acid addition. Experiments for stirred ash suspensions utilizing a three compartment cell setup where the anode, cathode and stirred suspension are separated by ion exchange membranes are reported. Simplifying this experimental setup by removing the anion exchange membrane brings the anode in direct contact with the stirred ash suspension. Through this adjustment, half-reactions at the anode contribute to the acidity of the stirred suspension resulting in increased dissolution of both phosphorus and heavy metals (Cd, Cu, Cr, Pb, Zn, Ni) and better separation of most heavy metals from the stirred ash suspension. When the ash is suspended in an acidic solution, these effects increase significantly in early stages of the experiments. The combination of ED in a two compartment setup and initial acidification of the stirred suspension is most effective in dissolving of phosphorus and separation of heavy metals. In this setup, up to 96% of the phosphorus in the ash was dissolved after 7 d. Using the three compartment setup and initially suspending the ash in distilled water, resulted in 53% dissolution of the total recovered phosphorus after 7 d.